Analysis of the influence of handset phone position on RF exposure of brain tissue. Issue 8 (26th September 2014) - Ghanmi, Amal; Varsier, Nadège; Hadjem, Abdelhamid; Conil, Emmanuelle; Picon, Odile; Wiart, Joe
<x xml:space="preserve">Abstract</x> Exposure to mobile phone radio frequency (RF) electromagnetic fields depends on many different parameters. For epidemiological studies investigating the risk of brain cancer linked to RF exposure from mobile phones, it is of great interest to characterize brain tissue exposure and to know which parameters this exposure is sensitive to. One such parameter is the position of the phone during communication. In this article, we analyze the influence of the phone position on the brain exposure by comparing the specific absorption rate (SAR) induced in the head by two different mobile phone models operating in Global System for Mobile Communications (GSM) frequency bands. To achieve this objective, 80 different phone positions were chosen using an experiment based on the Latin hypercube sampling (LHS) to select a representative set of positions. The averaged SAR over 10 g (SAR10 g) in the head, the averaged SAR over 1 g (SAR1 g) in the brain, and the averaged SAR in different anatomical brain structures were estimated at 900 and 1800 MHz for the 80 positions. The results illustrate that SAR distributions inside the brain area are sensitive to the position of the mobile phone relative to the head. The results also show that for 5–10% of the studied positions the SAR10 g in the head and the SAR1 g in the brain can be 20% higher than the SAR estimated for the standard cheek position and that the Specific Anthropomorphic Mannequin (SAM) model is conservative for 95% of all the studied positions. Bioelectromagnetics 35:568–579, 2014. © 2014 Wiley Periodicals, Inc.